PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN WORKING CAPITAL TURNOVER TERHADAP RETURN ON ASSET PADA PT.PERKEBUNAN NUSANTARA III PERIODE 2015-2017 - Sihotang, Gresela Patresia; br. Ginting, Emi Christin (EDUTECH CONSULTANT, 2019)
This research was conducted at the company PT. Perkebunan Nusantara III Medan, the purpose of this research is to analyze its influence current ratio, debt to equity ratio and working capital turnover to return on assets at PT. Nusantara III Medan Plantation 2015-2017 Period. The method in this study is a quantitative method using financial statements and the sample of this study is 36 samples, namely from the period 2015-2017 and taken with documentation techniques. This study uses secondary data and hypothesis testing of this study was carried out using multiple linear regression analysis, the test results of the coefficient of determination (adjusted R2) indicate that simultaneous ability current ratio variables, debt to equity ratio and working capital turnover to explain return on assets is 40% while the. remaining 60% is influence by other variabel. On the results of simultaneous research (F test) shows that the current ratio, debt to equity ratio and working capital turnover have a significant and positive effect on return on assets in the company PT. Perkebunan Nusantara III Medan period 2015-2017 and the results of the research partially (T test) show that the current ratio does not have a positive and significant effect on return on assets and while the debt to equity ratio has a positive and significant effect on return on assets but not working capital turnover positive but significant effect.